Pd-catalyzed decarboxylative Heck vinylation of 2-nitrobenzoates in the presence of CuF2 - Gooßen, Lukas J.; Zimmermann, Bettina; Knauber, Thomas (Beilstein Journal of Organic Chemistry, 2010)
A new protocol for the decarboxylative Heck vinylation of benzoic acids is disclosed. In the presence of a catalyst system generated in situ from Pd(OAc)2 (2 mol %), CuF2 (2 equiv), and benzoquinone (0.5 equiv) in NMP, a wide range of olefins were coupled with various 2-nitrobenzoates at 130 °C with the release of carbon dioxide to afford the corresponding vinyl arenes in good yields.
Keywords: carboxylic acids; copper; decarboxylation; Heck vinylation; palladium